2019
DOI: 10.1371/journal.pone.0225240
|View full text |Cite
|
Sign up to set email alerts
|

The Polish version of the Cultural Intelligence Scale: Assessment of its reliability and validity among healthcare professionals and medical faculty students

Abstract: BackgroundHealthcare professionals and students of medical faculties in Poland increasingly encounter culturally diverse patients. It is necessary to support the development of cultural intelligence in order to improve the medical care provided to patients from different cultural backgrounds. At present there are no standardized tools in Poland that can accurately and reliably assess cultural intelligence, which is defined by Ang et al. as “an individual’s capability to function and manage effectively in cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 45 publications
(68 reference statements)
5
25
0
2
Order By: Relevance
“…Study 5 showed that self-esteem is only related to motivational CQ. Similar conclusions are presented by Barzykowski et al (2019), although in this case, there are also no previous studies with which to make comparisons.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Study 5 showed that self-esteem is only related to motivational CQ. Similar conclusions are presented by Barzykowski et al (2019), although in this case, there are also no previous studies with which to make comparisons.…”
Section: Discussionsupporting
confidence: 80%
“…Their knowledge can result both from experience as well as from directed cognitive activity. Such individuals also display an aboveaverage ability to direct their attention and energy towards knowing and understanding multicultural situations (Barzykowski, Majda, Szkup, & Przyłęcki, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social desirability bias associated with self‐report questionnaires may have influenced results despite the anonymous nature of our survey. While two thirds of respondents felt competent or very competent, the actual proportion may be smaller (Barzykowski, Majda, Szkup & Przyłęcki, 2019). Additionally, the Cronbach’s alpha score obtained on the translated version was not as high as expected.…”
Section: Limitationsmentioning
confidence: 99%
“…Currently, for the purposes of testing cultural competence of the Polish nursing community, several scales have been adapted, i.e. the Cultural Intelligence Scale (CQS) by Ang, Van Dyne and Koh, which makes it possible to estimate cultural intelligence, that is to say, the individual's ability to deal effectively in situations of cultural diversity [20,21]. This same team has adapted and assessed the psychometric values of The Cross-Cultural Competence Inventory, permitting an evaluation of the seven dimensions of intercultural competence, i.e.…”
Section: Plos Onementioning
confidence: 99%